Transgenerational effects of childhood conditions on third generation health and education outcomes - Gerard J. van den Berg; Pia R. Pinger (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
This paper examines the extent to which pre-puberty nutritional conditions in one generation affect productivity-related outcomes in later generations. Recent findings from the biological literature suggest that age 8-12 is a critical period for male germ cell development. We build on this evidence and investigate whether undernutrition at that age biologically transmits to children and grandchildren. Our findings indicate that third generation males (females) tend to have higher mental health scores if their paternal grandfather (maternal grandmother) was exposed to a famine during preadolescence. These effects seem to result from a biological shock and are not driven by social processes.
Keywords: I12; J11; 330; famine; transgenerational transmission; epigenetics; mental health; education; long-run effects; nutrition; intergenerational effects; slow-growth period